In Silico Study of The Active Compound of The Sambiloto Plant (Andrographis paniculata Ness.) on HIV-1 Protease Receptors - Tri Maratuzzakiyah; Rosario Trijuliamos Manalu; Tiah Rachmatiah (East Asian Journal of Multidisciplinary Research, 2022)
Human Immunodeficiency Virus (HIV) is a virus that attacks the immune system. Sambiloto (Andrographis Paniculata Ness) is a medicinal plant that has some active coumpunds and is used to prevent and treat some diseases. The purpose of this study was to determine candidate active compounds from sambiloto plant that able to inhibit the work of HIV-1 protease enzyme using the Insilico method. The data of chemical compound of sambiloto was obtained from pubchem site and the structure of HIV-1 protease receptor got from Protein Data Bank with the code PDB 1D4H. The molecular docking results showed bisandrographolide and phytol have potential as anti-HIV drugs compared to amprenavir as a comparison ligand.